2016
DOI: 10.1186/s12978-016-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a symphysis-fundal height chart developed for pregnancy complicated by diabetes and hyperglycemia: an observational study

Abstract: BackgroundThe present study validates a symphysis-fundal height chart (SFH-chart) for pregnant women with type 2 diabetes mellitus (DM2), gestational diabetes mellitus (GDM) and mild gestational hyperglycemia (MGH) attending at the Diabetes and Pregnancy Reference Service of the Botucatu Medical School, UNESP, Brazil.MethodsA cross-sectional study was carried out to evaluate the performance of the specific FHC in predicting small (SGA) and large (LGA) for gestational age newborns (NB). We evaluated 206 pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The SFH chart shows high performance in predicting both SGA and LGA newborns of DM-2, GDM and MGH mothers. These findings support the internal validation of the SFH chart, which may be implemented in the prenatal care of patients with diabetes and pregnancy [12]. The SFH measurement is primarily practiced to detect fetal intrauterine growth restriction (IUGR).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The SFH chart shows high performance in predicting both SGA and LGA newborns of DM-2, GDM and MGH mothers. These findings support the internal validation of the SFH chart, which may be implemented in the prenatal care of patients with diabetes and pregnancy [12]. The SFH measurement is primarily practiced to detect fetal intrauterine growth restriction (IUGR).…”
Section: Discussionsupporting
confidence: 59%
“…B-ultrasonography, the symphysis-fundal height (SFH) chart and abdominal circumference (AC) measurements are monitoring approaches that are used routinely in departments of obstetrics and gynecology. Several studies have revealed that BMI, obesity, SFH and AC are associated with fetal weight, and these parameters are commonly used to predict fetal size and select a safe delivery method [10][11][12]. However, BMI, SFH and AC are not powerful enough for the diagnosis of macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…They have clinical significance for predicting infant size and as a reflection of the pregnant woman's nutritional status. These findings support the internal validation of the SFH chart, which may be implemented in the prenatal care of patients with diabetes and pregnancy [12]. However, one reference shows that there is no evidence that SFH is useful to identify macrosomia [13].…”
Section: Discussionmentioning
confidence: 58%
“…They have clinical significance for predicting infant size and as a reflection of the pregnant woman's nutritional status for reference. These findings support the internal validation of the SFH chart, which may be implemented in the prenatal care of patients with diabetes and pregnancy [12]. But the reference shows that there is no evidence that SFH is useful to identify macrosomia [13].…”
Section: Discussionmentioning
confidence: 62%
“…B-ultrasonography, the symphysis-fundal height (SFH) chart and abdominal circumference (AC) measurements are monitoring approaches that are used routinely in departments of obstetrics and gynecology. Several studies have revealed that BMI, obesity, SFH and AC are associated with fetal weight, and these parameters are commonly used to predict fetal size and select a safe delivery method [10][11][12]. However, BMI, SFH and AC are not powerful enough for the diagnosis of macrosomia [13].…”
Section: Introductionmentioning
confidence: 99%